Kansas Land Prices and Cash Rental Rates - Dhuyvetter, Kevin C.; Kastens, Terry L. (My University, 2008)
This farm management guide reports Kansas land prices and cash rental rates for 1989-2008. The data is meant to be useful to farm managers.
MF1100_2008_10
Keywords: MF1100; Economics; MF